Duty of care an executive guide for corporate boards in the digital era - Calder, Alizabeth 1958- (Wiley, 2019)
An essential guide for board members and executives who need to understand the impact of digital on their thinking and decision making Duty of Care: An Executive's Guide for Corporate Boards in the Digital Era offers a much needed guide for board directors and leaders who need to get up-to-speed and close their digital knowledge gap in order to make the right decisions about digital technology investment and deployments. Written in easy-to-read language, this book targets directors and executives who want to protect themselves from risks ranging from massive cyber security breaches to digital infrastructure investment mistakes. Most board members don't have the information they need to understand digital information systems, modern high-speed networks, and rapidly evolving software and hardware ecosystems. They also don't have the time to seek out or filter what they need from the many diverse sources. Their lack of knowledge can lead to disastrous decisions that can cost shareholders billions of dollars in lost income or risk liability. Written by a globally recognized experienced business executive and expert in cyber security, this essential guide and blueprint can serve the strategic and governance needs of every company. -Written by an noted expert in cyber security and digital strategy -Designed to be accessible for board members unfamiliar with digital technology, with case studies and smart questions to support leaders on every topic -Helps board directors, corporate officers, and corporate investors with the digital knowledge needed to make informed decisions Duty of Care is a comprehensive yet accessible book that helps board members close their "digital knowledge gap" in order to better serve their corporations
Keywords: Board of directors; Corporate Governance; Boards of directors; Corporate governance; Information technology / Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic books